Dexmedetomidine prevents hemorrhagic brain injury by reducing damage induced by ferroptosis in mice. (25th September 2022) - Liu, Man-Jia; Zhao, Xiao-Chun; Gong, He-Song; You, Yu-Qing; Li, Jing-Ya
Highlights: We investigated the effect of preoperative DEX on intracerebral hemorrhage (ICH) DEX reduced the damage induced by ferroptosis after ICH in mice. DEX alleviated iron deposition and oxidative stress caused by ferroptosis. DEX could be useful to reduce ICH-related damage. Abstract: Intracerebral hemorrhage (ICH) is a devastating condition with significant morbidity and mortality for which few effective treatments are clinically available. After ICH, iron overload within the perihaematomal region can induce lethal reactive oxygen species (ROS) production and lipid peroxidation, which contribute to secondary brain injury. An iron-dependent form of non-apoptotic cell death known as ferroptosis was recently identified. Ferroptosis plays an important role in ICH pathology. It is characterized by an accumulation of iron-induced lipid ROS, which leads to intracellular oxidative stress. Dexmedetomidine (DEX), an α2-adrenergic agonist, is widely used for anesthesia, pain control, and intensive care unit sedation. DEX has numerous beneficial activities, including anti-inflammatory, anti-oxidative, and anti-cell death activities. Here, we established a mouse model of ICH using collagenase VII and evaluated the effect of DEX in preventing ICH-induced brain injury. Our study showed that administering DEX reduced the damage induced by ferroptosis after ICH by regulating iron metabolism, amino acid metabolism and lipid peroxidation processes.